Perbandingan efektivitas senyawa logam alkali sebagai zat cabut warna golongan reaktif pada batik - Babsel, Muhammad Cladio Aimar; Maghfiroh, Maghfiroh; Lestari, Rizki (Fakultas Teknik Universitas Pekalongan bekerjasama dengan Asosiasi Perajin dan Pengusaha Batik (APPBI), 2024)
In making batik, the color dyeing method sometimes produces colors that are not as desired. One way to remove color pigment is by unpluging color. Apart from that, unplug color can be used as a technique to produce decorative variations on fabric. Unplug color is used to take or remove color pigments that are already on the fabric to obtain the previous color. The use of color removal agents affects the color removal results. The aim of this research is to determine the appropriate level of cleanliness for the application of scrub on fabric that is removed using calcium hypochlorite, sodium hypochlorite, sodium hydrosulfite and potassium permanganate. The research method used is field observations carried out in areas that have color removal facilities, then from the results of the data obtained an experiment will be carried out with a recipe for a removal agent of 10 grams/liter with a removal time of 10 minutes. The experimental results showed that the removal agents for calcium hypochlorite, sodium hypochlorite and sodium hydrosulfite had a color that was lighter than the original color. Meanwhile, the potassium permanganate dissolving agent produces a color that is different from the direction of the original color.